'Just reading': the impact of a faster pace of reading narratives on the comprehension of poorer adolescent readers in English classrooms. (26th February 2018) - Westbrook, Jo; Sutherland, Julia; Oakhill, Jane; Sullivan, Susan
Abstract: Poorer adolescent readers are often regarded by teachers as unable to read whole narratives and given short, simplified texts, yet are expected to analyse every part in a slow laborious read‐through. This article reports on a mixed methods study in which 20 English teachers in the South of England changed their current practice to read two whole challenging novels at a faster pace than usual in 12 weeks with their average and poorer readers ages 12–13. Ten teachers received additional training in teaching comprehension. Students in both groups made 8.5 months' mean progress on standardised tests of reading comprehension, but the poorer readers made a surprising 16 months progress but with no difference made by the training programme. Simply reading challenging, complex novels aloud and at a fast pace in each lesson repositioned 'poorer readers' as 'good' readers, giving them a more engaged uninterrupted reading experience over a sustained period. However, the qualitative data showed that teachers with the additional training provided a more coherent faster read and better supported poorer readers by explicitly teaching inference, diagnosed students' 'sticking places' mid‐text and created socially cohesive guided reading groups that further supported weaker readers and also stretched the average/good readers.